Optimal Decay Rates for Kirchhoff Plates with Intermediate Damping - Bravo, J. C. V.; Oquendo, H. P.; Rivera, J. E. M. (Trends in Computational and Applied Mathematics, 2020)
In this paper we study the asymptotic behavior of Kirchhoff plates with intermediate damping. The damping considered contemplates the frictional and the Kelvin-Voigt type dampings. We show that the semigroup those equations decays polynomially in time at least with the rate t^{-1/(2-2θ)}, where θ is a parameter in the interval [0,1[. Moreover, we prove that this decay rate is optimal.